I subalterni e la religione in Gramsci. Una lettura dall’America Latina - Semeraro, Giovanni (International Gramsci Journal, 2023)
This contribution proposes an analysis of Gramsci’s notes on religion, in particular on Christianity’s and the catholic Church’s relation with the subaltern classes. We highlight his distinctions between the “utopian” dimensions which Christianity contains and the feudal structure of the Church. To this latter, which maintains the popular masses in a condition of subalternity, Gramsci counterposes the “philosophy of praxis” directed towards self-government and the conquest of hegemony by the subaltern classes. In the second part of the article, we establish a counterpoint between Gramsci’s considerations on religion (and the catholic Church) and the role of the subalterns in Christianity as redeemed by Liberation Theology in Latin America. Here indeed, over the last few decades, significant sectors of Christians, making use of the analytical instruments provided by Marxism and by the thought of Gramsci, have made their ‘choice for the poor’, thereby giving religion and politics a new configuration.